Parental Involvement and Socio-emotional Skills of the Kindergarten Pupils: A Correlational Study - Nurhajija K. Bisin; Fatima Amisha I. Yusop; Al-Rashiff Hamjilani Mastul (Buletin Edukasi Indonesia, 2025)
Academic achievement does not guarantee success in school; one must also work on establishing the students' socio-emotional abilities to interact with teachers and peers. Socio-emotional development describes the ways in which children learn to communicate and express their emotions, form bonds with others, and engage in social abilities. Prioritizing socio-emotional development in preschool and kindergarten is essential. The purpose of this study is to examine the influence of parental involvement and socio-emotional skills of the kindergarten pupils of Pagasinan Elementary School. This study utilized quantitative descriptive research design to investigate the socio-emotional skills of kindergarten pupils in Sanga-Sanga, Bongao, Tawi-Tawi. The research specifically examined the influence of parental involvement on the socio-emotional skills of these young learners, utilizing quantitative research methods for data analysis and interpretation. Parents of Pagasinan Elementary School are highly involved in various aspects of their children’s education. This includes fulfilling basic obligations, maintaining school-to-home communication, participating in school activities, and engaging in home learning activities. The kindergarten pupils possess strong socio-emotional skills as perceived by their teachers. Specifically, pupils show a high level of self-awareness and advanced level of self-management. There is moderate positive and statistically significant correlation between parents’ involvement and the socio-emotional skills of kindergarten pupils. As parents’ involvement, so does the socio-emotional of the pupils.